CHARACTERISTICS OF CHILDREN IN THE QUR'AN - Dewi Murni; Ahmad Nur Fathoni (Program Studi Ilmu Al-Qur’an dan Tafsir Fak. Ilmu Agama Islam Universitas Islam Indragiri, 2022)
This research aims to examine more deeply about children, especially the characteristics of children in the Qur'an and the implications of its meaning in the context of parenting. Children are a gift as well as a trust that aresent by Allah to His servants who will be asked the responsibility in the afterlife. Parents responsibilities is to provide education to children from early age.Development in early childhood is largely determined by the environment and family. This study explains that the family is the first place where children get education. The character and personality of children are formed in the family. Parents actually must have concepts or provisions for educating their children which include moral or character education, science education, religious education, justice, and giving attention and affection to them. This study examines children's terms such as al walad , al ibn, al bint, dzurriyah, as Shobiyu, at thifluand al ghulamu. On the other hand, it also discusses the types of children's characters in the Qur'an and the implications of their meaning for parenting, therefore, this research will be possible to study in more detail.